Nothing is Singular Akram Khan and Sidi Larbi Cherkaoui's collaboration reviewed - Roy, Sanjoy (Dance Books Ltd., Alton,Hampshire (UK), 2005)
Review of Akram Khan and Sidi Larbi Cherkaoui. Each tiny hesitation and gesture is precisely synchronised, to eerie and sometimes comic effect. This intimation of death is simple on the surface but also turbulent with undercurrents. PALABRAS CLAVE: Akram Khan, Sidi Larbi Cherkaoui, kathar, contemporary dance.